6 years experience in the Management of Myelomeningocele : History , Research, Clinical and Future Direction in Maesot General Hospital - Thanaphiphatchai, Kanlaya (Thai Journal of Neurological Surgery, 2025)
Background: Myelomeningocele is a complex congenital anomaly that was found in Maesot hospital. It is necessary to prevent and reduce any risk factors. Prenatal diagnosis, treatment, postoperative care of complications, sequelae and long-term follow-up are important factors to prevent mortalities and morbidities. Maesot Hospital still lacks these data. Objective: We aim to study the risk factors and outcome of myelomeningocele in the context of Maesot Hospital by conducting studies ranging from antenatal care and prenatal diagnosis, including maternity care, surgical treatment, surveillance for potential complications, and long-term treatment. Methods: We incorporated a group of patients from 2015 - 2020 to find a suitable care guideline to minimize disability and promote a good quality of life. We conducted a retrospective study by reviewing the medical records of patients with myelomeningocele who received treatment at the Maesot Hospital from 2015 – 2020. Results: Between January 2015 and December 2020, there were 8 cases of myelomeningocele, with seven males and one female. The most common affected region lesion level was lumbosacral area in 4 cases (50%); all had come with a lump, of which 7 casas (87.5%) were ruptured. The co-existing disorder and the most common complication was hydrocephalus, which was found in 7 cases (87.5%), of which 6 cases (75%) received permanent cerebrospinal fluid drainage surgery (ventriculoperitoneal shunt) while the remaining one case can compensate the hydrocephalus. All patients were treated with various surgical procedures. Factors affecting treatment and prognosis are body weight, time from birth until treatment was established, the degree of hydrocephalus, antibiotics prescription, and ruptured or unruptured lesion. Sometimes myelomeningocele was disease that can be prevented, treated, and reduced complications. Thoroughly history taking with completing medical records are keys for the healthcare provider to analyze the overall picture of these patients. Conclusions: Due to sequelae in multiple systems, it is good to have guidelines in caring and set up a holistic health clinic to take care of inpatients and outpatients, allowing this group of patients to receive complete treatment.